Pioneering family in the Klondike, Alaska, ca. 1898 - Hegg, Eric A., 1867-1948
Family poses outdoors, ca. 1897-1900. Man, his Alaskan Indian wife & their children, in parkas, heavy coats and mukluks. Caption on image: Pioneers. Klondyke Y.T. Hegg & Co. Photo